PENINGKATAN KAPASITAS PENGELOLAAN SUMBERDAYA LOKAL BERBASIS SDGs DESA TONGKONUNUK. SULAWESI TENGAH - muhammad sayuti; Hasanuddin hasanuddin; Eduart Wolok; Sunardi Sunardi; Syarifuddin Achmad (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2022)
Sustainable Development Goals (TPB)/Sustainable Development Goals (SDGs) are development that maintains sustainable improvement of the economic welfare of the community, development that maintains the sustainability of community social life, development that maintains environmental quality and development that ensures justice and the implementation of governance capable of maintaining improving the quality of life from one generation to the next. The objectives of implementing the Village Thematic Community Service Program to Build UNG in Tongkonunuk Village are as follows: 1) Assist in providing the Tongkonunuk village community database through data collection on SDGs. 2) Assist in implementing the health protocol in the Tongkonunuk village community. 3) Helping the community to have a clean and healthy environment through clean Friday activities. 4) Help provide clean and healthy water for the people of Tongkonunuk village through the installation of clean water pipes. 5) Help reactivate the village youth forum (Karang Taruna) Tongkonunuk Village. This method is systematically carried out by assisting village officials in terms of capacity building and management to accelerate the achievement of sustainable development by looking at the SDGs topology applied by Tongkonunuk village, Pagimana sub-district, Luwuk district